English to Indonesian Interference in Tiktok Commentaries - Widyadhana Nur Hidayat; Sri Raini; Elisa Aulia; Elsa Salsabila; Iis Lisnawati (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
The objective of this study is to examine the manifestations and underlying causes of English to Indonesian interference in TikTok comments from a psycholinguistic perspective, with implications for Indonesian language education in the digital era. The focus on linguistic interference, encompassing lexical, grammatical, and phonological dimensions, is predicated on its reflection of the cognitive dynamics exhibited by bilingual speakers in the context of digital communication. The research employed a qualitative approach, utilizing a content analysis design to examine 50 comments from 10 popular TikTok videos in Indonesia (with a minimum of 50,000 views and 5,000 interactions) uploaded between January and April 2025. The data were collected manually through purposive sampling based on the criteria of comments containing English elements. The data were then analyzed with guidelines based on Weinreich's (1953) framework, and the results were validated through researcher triangulation (Cohen's Kappa coefficient = 0.85). The results indicated that 100% of the comments exhibited interference, with distribution: lexical (56.8%), phonological (16.2%), syntactic (16.2%), and morphological (10.8%) interference. Lexical interference, exemplified by words such as "relate," "exactly," and "post," has become a predominant phenomenon in digital culture, largely attributable to the efficiency of digital communication. The context of the video, which can be categorized as educational, motivational, or entertainment, influences the type of interference observed. Lexical interference is more prevalent in educational videos, while syntactic interference is more common in entertainment videos. The findings support the Bilingual Interactive Activation Model (Dijkstra & Van Heuven, 2002), demonstrating the simultaneous activation of English and Indonesian in speakers' minds. This research underscores the necessity for Indonesian language teaching strategies that are responsive to digital bilingualism. Keywords : language interference, psycholinguistics, TikTok, bilingualism